Comparative analysis of pathogenic and nonpathogenic Fusarium oxysporum populations associated with banana on a farm in Minas Gerais, Brazil. (23rd October 2017) - Deltour, P.; França, S. C.; Heyman, L.; Pereira, O. L.; Höfte, M.
Abstract : Fusarium wilt is one of the most devastating diseases on banana. The causal agent, Fusarium oxysporum f. sp. cubense (Foc) is genetically diverse and its origin and virulence are poorly understood. In this study, pathogenic Foc isolates and nonpathogenic F. oxysporum isolates from Minas Gerais in Brazil were compared using EF‐1 α and IGS sequences. This allowed the examination of the origin and evolutionary potential of Foc in a country outside the region of origin of the banana plant. Two different sequence types were found among Foc isolates. One appeared to be of local origin because it was identical to the sequence type of the largest group of nonpathogenic isolates. To explore if the 'local' Foc isolates had acquired pathogenicity either independently through coevolution with the host, or through horizontal gene transfer (HGT) of pathogenicity genes from other, probably introduced, Foc isolates, the presence and sequence of putative SIX effector genes were analysed. Homologues of SIX1, SIX3 and SIX8 were found. SIX1 sequences were identical and exclusively found in all pathogenic isolates, while variable ratios of sequences of multicopy gene SIX8 were found among nonpathogenic and different pathogenic isolates. This observation supports the HGT hypothesis. Horizontal transfer of genes between isolates of F. oxysporum has important implications for the development of reliable diagnostic tools and effective control measures. Full genome sequencing is required to confirm HGT and to further unravel the virulence mechanisms of forma specialis cubense .